A Database-Centric CSPM Framework for Securing Mission-Critical Cloud Workloads - Veeravenkata Maruthi Lakshmi Ganesh Nerella (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Cloud Security Posture Management (CSPM) has become increasingly vital as organizations move their critical database workloads to the cloud. CSPM provides a proactive approach to identifying, managing, and remediating security risks within cloud environments, focusing on safeguarding sensitive data and ensuring compliance with industry regulations. This research delves into CSPM’s role in securing mission-critical database workloads, emphasizing its core components, strategies, and best practices. By implementing CSPM tools, organizations can gain visibility into their cloud security posture, automate compliance checks, and detect vulnerabilities in real-time. The paper explores key CSPM features, such as configuration assessment, vulnerability scanning, and automated remediation, which help mitigate risks such as data exposure, insider threats, and compliance failures. To extend existing approaches, we propose a novel four-layered Database-Centric CSPM Framework (DC-CSPMF), specifically designed to address database-level misconfigurations, privilege drift, and workload-aware remediation strategies. The framework introduces enhanced posture management tailored to relational and NoSQL cloud databases, filling a critical gap in conventional CSPM solutions. The research also highlights the challenges organizations face when securing cloud-based databases, particularly the complexities of managing dynamic cloud environments and regulatory requirements. A case study approach is employed to examine real-world examples of CSPM implementations, offering insights into its practical applications and effectiveness in improving cloud security. The findings suggest that CSPM—when augmented with the proposed DC-CSPMF—offers a robust strategy for maintaining the security, availability, and compliance of mission-critical databases in the cloud, ensuring the integrity of business operations while minimizing potential risks. DOI: https://doi.org/10.17762/ijisae.v10i1.7782